Patterns and predictors of smokeless tobacco use among adults in Bangladesh: findings from the International Tobacco Control (ITC) Bangladesh survey. - Abu S Abdullah; Pete Driezen; Ummul H Ruthbah; Nigar Nargis; Anne C K Quah; Geoffrey T Fong (PLoS ONE)
Background Although smokeless tobacco (SLT) use is prevalent in South Asian countries including Bangladesh, information about the pattern and correlates of SLT use is scarce. This study described the pattern and predictors of SLT use among Bangladeshi adults. Methods The data for this study were derived from the International Tobacco Control Policy Evaluation Bangladesh (ITC BD) Survey, a prospective cohort survey of a nationally representative sample of smokers and non-smokers, conducted during November 2011 and May 2012. The study included 5522 adults aged 15 or above. We used multiple logistic regression models to identify predictors of SLT use. Results Of the respondents (N = 5522), 20% were SLT users. In general, SLT use was significantly higher among women, the illiterate and residents of the Dhaka slums or non-tribal/non-border areas outside Dhaka; SLT use increased with age. Several attitudinal factors were also associated with SLT use. Multivariable logistic regression analyses revealed several predictors of SLT use: being female (OR = 1.96, 95% confidence interval, CI: 1.18-3.24), an increasing age, being a resident of a Dhaka slum (OR = 5.86; 95% CI: 3.73-9.21) or non-tribal/non-border areas outside Dhaka (OR = 3.42; 95% CI: 1.94-6.03), being illiterate (OR = 3.37; 95% CI: 1.99-5.71), holding positive opinion towards societal approval of SLT use (OR = 5.84; 95% CI: 3.38-10.09), holding positive opinion towards SLT use by women (OR = 2.63; 95% CI: 1.53-4.54), believing that SLT is addictive (OR = 2.96; 95% CI: 1.51-5.81), and believing SLT is less harmful than bidi (OR = 2.22; 95% CI: 1.36-3.62). Conclusion The findings suggest that coordinated efforts of governmental and non-governmental organizations, targeting both smoked tobacco and SLT use reduction and cessation, could be modified to reach each level of population including those who are marginalized, female, less educated and elderly. As most tobacco control programs in Bangladesh target mainly cigarette or bidi smoking, coordinated programs are needed that will also include SLT use within the tobacco control policy and prevention strategies.